Multivariate and network meta-analysis of multiple outcomes and multiple treatments: rationale, concepts, and examples. (13th September 2017) - Riley, Richard D; Jackson, Dan; Salanti, Georgia; Burke, Danielle L; Price, Malcolm; Kirkham, Jamie; White, Ian R
Abstract : Organisations such as the National Institute for Health and Care Excellence require the synthesis of evidence from existing studies to inform their decisions—for example, about the best available treatments with respect to multiple efficacy and safety outcomes. However, relevant studies may not provide direct evidence about all the treatments or outcomes of interest. Multivariate and network meta-analysis methods provide a framework to address this, using correlated or indirect evidence from such studies alongside any direct evidence. In this article, the authors describe the key concepts and assumptions of these methods, outline how correlated and indirect evidence arises, and illustrate the contribution of such evidence in real clinical examples involving multiple outcomes and multiple treatments